2020
DOI: 10.21203/rs.3.rs-39964/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long Non-Coding RNA GATA6-AS1 Inhibits Proliferation and Promotes Apoptosis of Lung Adenocarcinoma Through Sponging miR-331-3p and Regulating SOCS1/JAK2/STAT3 Pathway

Abstract: Abstract Background: Accumulating evidence has indicated the remarkable roles of long non-coding RNAs (lncRNAs) as oncogenes or tumor suppressors in many malignancies. The involvement of lncRNA GATA6-AS1 in cancers remains largely undiscovered. Herein, our research was aimed at elucidating the function and mechanism of GATA6-AS1 in lung adenocarcinoma (LUAD).Methods: Gene expression was measured through qRT-PCR and WB. Cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(22 reference statements)
1
0
0
Order By: Relevance
“…In our study, the positive correlation between PTEN and GATA6-AS1 in GC was identified. According to the previous study, AKT signaling pathway is crucial in regulating GC [41,42]. In our research, western blot indicated that phosphorylated AKT level was reduced by the overexpression of GATA6-AS1 but upregulated by the downregulation of PTEN or addition of SF1670 (PTEN inhibitor).…”
Section: Discussionsupporting
confidence: 52%
“…In our study, the positive correlation between PTEN and GATA6-AS1 in GC was identified. According to the previous study, AKT signaling pathway is crucial in regulating GC [41,42]. In our research, western blot indicated that phosphorylated AKT level was reduced by the overexpression of GATA6-AS1 but upregulated by the downregulation of PTEN or addition of SF1670 (PTEN inhibitor).…”
Section: Discussionsupporting
confidence: 52%